2019
DOI: 10.3390/molecules24224095
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Novel Compounds Against Malaria: Quinolines, Triazolpyridines, Pyrazolopyridines and Pyrazolopyrimidines

Abstract: Based on medicinal chemistry tools, new compounds for malaria treatment were designed. The scaffolds of the drugs used to treat malaria, such as chloroquine, primaquine, amodiaquine, mefloquine and sulfadoxine, were used as inspiration. We demonstrated the importance of quinoline and non-quinoline derivatives in vitro with activity against the W2 chloroquine-resistant (CQR) Plasmodium falciparum clone strain and in vivo against Plasmodium berghei-infected mouse model. Among the quinoline derivatives, new hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 56 publications
(67 reference statements)
0
33
0
Order By: Relevance
“…Antimalarial evaluation of twenty six [1,2,4]triazolo[1,5- a ]pyrimidine derivatives 214 ( Fig. 42 ) against chloroquine-resistant W2 strain of P. falciparum revealed that compounds 214a-d displayed most effective antimalarial activity with IC 50 in the range of 0.023–0.55 μM [ 194 ].…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…Antimalarial evaluation of twenty six [1,2,4]triazolo[1,5- a ]pyrimidine derivatives 214 ( Fig. 42 ) against chloroquine-resistant W2 strain of P. falciparum revealed that compounds 214a-d displayed most effective antimalarial activity with IC 50 in the range of 0.023–0.55 μM [ 194 ].…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…Pyrazolo [1,5-a]pyrimidines are a class of structurally challenging compounds with interesting properties [75], including promising antibacterial activity, as seen, for example, in preliminary studies against Mycobacterium tuberculosis [76,77], as well as antiparasitic activity against Plasmodium spp. [78,79] and other protozoans, such as Trypanosoma spp. and Leishmania spp.…”
Section: Pyrazolo[15-a]pyrimidinesmentioning
confidence: 99%
“…Pyrazolopyridines, in which a group of three nitrogen atoms is incorporated into a bicyclic heterocycle, are privileged medicinal scaffolds, often utilized in drug design and discovery regimes (Kumar et al, 2019). Owing to the possibilities of the easy synthesis of a literally unlimited number of a combinatorial library of small organic molecules with a pyrazolopyridine scaffold, there has been enormous interest in these molecules among medicinal chemists (Kumar et al 2019;Pinheiro et al 2019;Hardy, 1984). Indeed, molecules with pyrazolopyridine in the core structure exhibit multifaceted medicinal properties such as anti-microbial, anti-viral, antifungal, anti-hypertensive, analgesic, antiquorum-sensing, anticancer, anti-inflammatory, anti-Alzheimer's, anti-diabetic, anti-nociceptive, anti-tuberculosis and anti-leishmanial activities (Hardy, 1984;Hawas et al, 2019;de Mello et al, 2004;El-Gohary et al, 2019;El-Gohary & Shaaban, 2018).…”
Section: Chemical Contextmentioning
confidence: 99%